2016
DOI: 10.1007/s11250-016-1001-1
|View full text |Cite
|
Sign up to set email alerts
|

Apple peel waste as a natural antioxidant for heat-stressed broiler chickens

Abstract: This study was conducted to evaluate the effects of processed apple peel waste (APW), alone or in combination with an enzyme, as a natural antioxidant on broiler chickens under heat stress. A total of 360 unsexed, 28-day-old broilers were assigned to 6 dietary treatments with four replicates (15 broilers per pen). The experiment consisted of a 3 × 2 factorial arrangement with three levels of apple peel waste (0, 50 or 100 g/kg of diet) and two levels of enzyme (0 or 500 mg/kg, ZY Multi(®)). Inclusion of 100-g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…As mentioned previously body weight of broilers in different rearing phases affected by DAP and interaction effect of DAP and enzyme supplementation in their diets (P < 0.05). Similar to obtained results, Heidarisafar et al (2016) observed that 50 g/kg apple peel waste caused to similar body weight to control group, and inclusion of 100 g/kg apple peel waste decreased body weight of broilers at 42 days of age. Also, they observed that adding multi enzyme to broiler diet had no effect on body weight of broilers at 42 or 49 days of age, which is disagree with obtained results in recent study.…”
Section: Performance Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…As mentioned previously body weight of broilers in different rearing phases affected by DAP and interaction effect of DAP and enzyme supplementation in their diets (P < 0.05). Similar to obtained results, Heidarisafar et al (2016) observed that 50 g/kg apple peel waste caused to similar body weight to control group, and inclusion of 100 g/kg apple peel waste decreased body weight of broilers at 42 days of age. Also, they observed that adding multi enzyme to broiler diet had no effect on body weight of broilers at 42 or 49 days of age, which is disagree with obtained results in recent study.…”
Section: Performance Parameterssupporting
confidence: 89%
“…Incorporation of fruit by-products with high fiber seemingly affects birds to modify their feed intake and preserve adequate energy consumption. The excessive use of fiber sources may also increase the viscosity of intestinal content and decreases bioavailability of nutrients (Heidarisafar et al 2016).…”
Section: Performance Parametersmentioning
confidence: 99%
“…This inference was supported because the administration of probiotic Lactobacillus spp. (Olnood et al, 2015) or processed apple peel waste (as a natural antioxidant) (Heidarisafar et al, 2016) increased the small intestinal weight (jejunum and ileum) of broiler chicks.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the supplementation of poultry feed with antioxidants can attenuate some of the detrimental effects (Heidarisafar et al 2016;Hosseini-Vashan et al 2016;Rafiee et al 2016). Much attention has been focused on combating the effect of oxidative stress induced by heat exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been focused on combating the effect of oxidative stress induced by heat exposure. In fact, the supplementation of poultry feed with antioxidants can attenuate some of the detrimental effects (Heidarisafar et al 2016;Hosseini-Vashan et al 2016;Rafiee et al 2016). However, the precise mechanisms underlying physiological and pathophysiological changes induced by heat exposure remain unknown.…”
Section: Introductionmentioning
confidence: 99%